Severity of asphyxia is a covariate of phenobarbital clearance in newborns undergoing hypothermia - Pokorná, Pavla; Posch, Lenka; Šíma, Martin; Klement, Petr; Slanar, Ondrej; van den Anker, John; Tibboel, Dick; Allegaert, Karel (The journal of maternal-fetal & neonatal medicine, 2019)
AIM: Phenobarbital (PB) pharmacokinetics (PK) in asphyxiated newborns show large variability, not only explained by hypothermia (HT). We evaluated potential relevant covariates of PK of PB in newborns treated with or without HT for hypoxic-ischemic encephalopathy (HIE). METHODS: Clearance (CL), distribution volume (Vd) and elimination half-life (t1/2) were calculated using one-compartment analysis. Covariates were clinical characteristics (weight, gestational age, hepatic, renal, and circulatory status), comedication and HIE severity [time to reach normal aEEG pattern (TnormaEEG), dichotomous, within 24 h] and asphyxia severity [severe aspyhxia = pH ≤7.1 + Apgar score ≤5 (5 min), dichotomous]. Student's t-test, two-way ANOVA, correlation and Pearson's chi-square test were used. RESULTS: Forty newborns were included [14 non-HT; 26 HT with TnormaEEG <24 h in 14/26 (group1-HT) and TnormaEEG ≥24 h in 12/26 (group2-HT)]. Severe asphyxia was present in 26/40 [5/14 non-HT, 11/14 and 10/12 in both HT groups]. PB-CL, Vd and t1/2 were similar between the non-HT and HT group. However, within the HT group, PB-CL was significantly different between group1-HT and group2-HT (p = .043). ANOVA showed that HT (p = .034) and severity of asphyxia (p = .038) reduced PB-CL (-50%). CONCLUSION: The interaction of severity of asphyxia and HT is associated with a clinical relevant reduced PB-CL, suggesting the potential relevance of disease characteristics beyond HT itself.
Keywords: Apgar Score; Analysis of Variance; Male; Hypothermia, Induced; Hypoxia-Ischemia, Brain; fenobarbital; hypothermia; Apgar skóre; Case-Control Studies; Prospective Studies; phenobarbital; mužské pohlaví; asfyxie novorozenců; mozková hypoxie a ischemie; Anticonvulsants; Severity of Illness Index; terapeutická hypotermie; novorozenec; Phenobarbital; pharmacodynamics; lidé; Metabolic Clearance Rate; ženské pohlaví; studie případů a kontrol; analýza rozptylu; Humans; pharmacokinetics; asphyxia; Infant, Newborn; antikonvulziva; stupeň závažnosti nemoci; Female; Asphyxia Neonatorum; Newborn; metabolická clearance; prospektivní studie